KONSELING INDIVIDUAL GURU BIMBINGAN DAN KONSELING TERHADAP PERILAKU PENGEMBANGAN POTENSI DIRI DI SMK NEGERI 4 BANJARMASIN - Suaibatul Aslamiyah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2017)
This study aims to investigate the implementation of individual counseling services terdahap self-development behavior in SMK Negeri sisiwa 4 Banjarmasin . Developing students' abilities optimally is a major responsibility of the educational activities . In this study the research method used is qualitative ethnographic approach. potential is the capabilities and qualities of a person that has not been used optimally. For that efforts to implement individual counseling services should be done seriously.